OPTIMASI PENDAPATAN PETANI MELALUI SYSTEM OF RICE INTENSIFICATION DI KABUPATEN INDRAMAYU - ,, Suphendi; Rustiadi, Ernan; Juanda, Bambang (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
Farmersâ Income Optimization through System of Rice Intensification in Indramayu District. One alternative to increase farmersâ income can be done by optimizing the planting methods. The purpose of this research is to analyze rice farming and optimal planting methods that maximize the farmersâ income. The study was conducted in Indramayu, West Java, involving 90 farmer respondents consisted of 60 conventional methods and 30 SRI methods. Using farming system and linear programming analysis, obtained:Â Firstly, the application of the System of Rice Intensification (SRI) on rice farming rice fields in Indramayu district is partially not provide optimal impact on farmers income.Â Secondly, Optimization of farm income SRI method of rice fields in Indramayu district predicted to occur if it is done on a regional scale with relatively large. Keywords: Income, optimization, conventional, SRI ABSTRAKSalah satu alternatif peningkatan pendapatan usahatani padi dapat dilakukan melalui optimalisasi metode tanam. Tujuan penelitian yaitu melakukan analisis usahatani padi sawah dan metode tanam optimal yang memaksimumkan pendapatan petani. Penelitian dilakukan di Kabupaten Indramayu, Jawa Barat, melibatkan 90 petani responden terdiri atas 60 petani padi konvensional dan 30 petani SRI. Dengan menggunakan analisis usahatani dan pemrograman linear, diperoleh hasil penelitian: Pertama, Penerapan System of Rice Intensification (SRI) pada usahatani padi sawah di Kabupaten Indramayu secara parsial belum memberikan dampak yang optimal terhadap pendapatan petani. Kedua, Optimalisasi pendapatan usahatani padi sawah metode SRI di Kabupaten Indramayu diprediksi akan terjadi jika dilakukan pada skala wilayah (hamparan) yang relatif luas.Kata kunci: Pendapatan, optimalisasi, konvensional, SRI